Colorectal Cancer Screening: What Is the Populations Opinion - Teixeira,Cristina (2018)
Background: Colorectal cancer (CRC) is the first cause of death by cancer in Portugal and mortality has been increasing in the last 30 years. Materials and Methods: During a raising awareness campaign performed by our Gastroenterology Department, in Setúbal, Portugal, an anonymous written questionnaire was developed and presented in order to evaluate the populations knowledge and attitude regarding CRC screening. Results: The following results were reported: 140 persons; mean age 54.6 years; 61.4% women; 22.1% had a family history of colorectal cancer. The main risk factors mentioned by the respondents were family history of CRC, previous history of intestinal polyps, and intestinal infection. Screening was considered useful by all respondents. About 60% of the respondents had been counselled, at least, on one screening technique, mainly by their general practitioner: colonoscopy in 31, fecal occult blood test in 44, and flexible sigmoidoscopy in 9. Most of the respondents had had the appropriate screening test, according to their age and family history. Fourteen of the respondents had not undergone the recommended screening. Their answers showed that this was due to fear of pain/ discovering a disease as well as embarrassment. Conclusion: Although the majority of the respondents were aware of the importance of CRC screening, results show that there are still several misconceptions about risk factors, fear, and reluctance concerning the screening techniques. Awareness actions are useful to clarify possible questions and inform the population in order to increase compliance with screening.